Representation Of Semiotics Analysis Of Moral Message In The Film “Iqro My Universe” - Hutauruk, Cindy Yulvika; Rasyid, Abdul; Monang, Sori (International Journal of Cultural and Social Science, 2022)
This research is entitled "Representation of the Semiotic Analysis of Moral Messages in the Iqro My Universe Film". The purpose of this study is to analyze the moral messages in the film "Iqro My Universe". The method used in this study is a qualitative descriptive method to explain the moral messages in the film. The research subject is the Iqro My Universe film with a duration of 231 minutes consisting of 80 scenes in total and 7 scenes as objects of analysis. The theory used to analyze this research is the Mass Communication Model, and Semiotic Analysis by Roland Barthes which consists of denotation, connotation, and myth. The results of this study found that in the Iqro My Universe film there are 7 scenes or scenes that contain moral messages. Some of the moral messages that are divided into sub-themes/scene scenes that the researcher chose include, among others; First, every effort we make will never betray the results. Second, the children's family where we come and return. Therefore, family is the most important aspect in our life. Third, don't ever judge someone just from their appearance. Because the eye can only see, feelings can be wrong and negative thinking is a bad attitude that must be eliminated. The film Iqro My Universe teaches us that weak social beings like us cannot be separated from two factors, namely fellow humans and God.